2021
DOI: 10.48550/arxiv.2110.00196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is Semantic Communication? A View on Conveying Meaning in the Era of Machine Intelligence

Abstract: In 1940s, Claude Shannon developed the information theory focusing on quantifying the maximum data rate that can be supported by a communication channel. Guided by this fundamental work, the main theme of wireless system design up until the fifth generation (5G) was the data rate maximization. In Shannon's theory, the semantic aspect and meaning of messages were treated as largely irrelevant to communication. The classic theory started to reveal its limitations in the modern era of machine intelligence, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 162 publications
(324 reference statements)
0
10
0
Order By: Relevance
“…Based on the literature [ 20 ], Basu et al (2012) provided a detailed explanation of the relationship between semantic entropy and information entropy, and they defined the concepts of semantic ambiguity and semantic redundancy [ 21 ]. In [ 22 ], Lan et al (2021) proposed that semantic communication can be divided into human-to-human, human-to-machine, and machine-to-machine sub-areas, which broadened the scope of semantic communication.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the literature [ 20 ], Basu et al (2012) provided a detailed explanation of the relationship between semantic entropy and information entropy, and they defined the concepts of semantic ambiguity and semantic redundancy [ 21 ]. In [ 22 ], Lan et al (2021) proposed that semantic communication can be divided into human-to-human, human-to-machine, and machine-to-machine sub-areas, which broadened the scope of semantic communication.…”
Section: Related Workmentioning
confidence: 99%
“…These Similarly, Zhang et al [20] proposed a new semantic system model with different layers as a Fig. 8: The novel layered architecture of semantic communication system [18].…”
Section: New Semantic Communication Frameworkmentioning
confidence: 99%
“…Strinati et al [17] indicated the role of semantic communications in 6G. Lan et al [18] classified semantic communications into human-to-human (Level 2), human-to-machine (Level 2 and Level 3), and machine-tomachine (Level 3) communications. Various potential applications of semantic communications are presented.…”
mentioning
confidence: 99%
“…We present a comprehensive analysis of current technical papers that apply SemCom in the latest 6G networks, and detail the features of SemCom and 6G. [6] Introduce the SemCom principles and two design approaches, i.e., layer-coupling design and end-to-end design using a neural network. Discuss specific techniques for different application areas of SemCom.…”
Section: Referencementioning
confidence: 99%